Are shadow system users the better IS users?-Insights of a lab experiment - Haag, Steffi; Eckhardt, Andreas; Bozoyan, Christiane (Proceedings of the 36th International Conference on Information Systems, Fort Worth, USA, 2015)
Prior research argues that the effective usage of a mandatory system varies with users' individual differences and engagement, the tasks carried out, and the system features applied. In this study, we analyze individual-level system usage to improve performance by adapting and expanding the number and configuration of systems in use. Thus, we address IT executives' increasing challenge of users deploying shadow systems besides or instead of the mandatory system. Integrating the existing knowledge of adaptive system use and shadow IT, we theoretically conceptualize individuals' shadow system usage, hypothesize cognitive, affective, and behavioral drivers, and its impact on job performance. Results of a lab experiment show that compared to nonusers, shadow system users are more intrinsically motivated, easier accept neutralization techniques, and perform significantly better, regarding both task output and task behavior. New insights are provided that deviant usage behavior improves not only task achievement, but also the mandatory system's functionality.
Keywords: IS usage; Intrinsic motivation; Perceived usefulness; Neutralization; Shadow IT; Performance